Determinants of mobile shopping behaviour: a study among students in UUM - Mohamad Noor Farez, Romli (2020)
Rapid changing in technology have resulted in altering the ways of shopping from physical to virtual which be access through online. This technology has a significant shift in the retail industry to ensure they can sustain and continue to have the customer by fast the implementation of web-based technology or even application build in on mobile device operating system which creates the new way of shopping being called mobile shopping. Besides, mobile shopping expands the consumers' power in shopping as well as involve the behaviour of the user. The purpose of this study is to know the determinants of mobile shopping behaviour based on a study among students in UUM. The research model was adapted and modified the framework from Technology Acceptance Model (TAM) and The Theory of Planned Behaviour (TPB) to match with objective of research and added with two potential variable which is satisfaction and trust to recognise the key determinants of mobile shopping behaviour. Overall the variables selected in this research model is perceived ease of use, perceived usefulness, satisfaction, attitude, trust, and subjective norm. The software of Statistical Package for Social Science (SPSS) is used to analyse a total of 377 of questionnaires among UUM’s students. The outcomes from analyses indicate that there is a significant relationship between the six independent variables which are perceived ease of use, perceived usefulness, satisfaction, attitude, trust, and subjective norm with the dependent variable, mobile shopping behaviour. Therefore, trust was found to be the most significant and strong variable that influential mobile shopping behaviour among students in UUM.